Public interest litigation: the need for a liberal approach of the rule of locus standi in Malaysia / Syakira Abdul Khair @ Khairuddin, Hazmida Harris Lee and Nik Nur Aisyah Nik Ab. Rahman - Abdul Khair @ Khairuddin, Syakira; Harris Lee, Hazmida; Nik Ab. Rahman, Nik Nur Aisyah (2011)
This paper is a research on the strict rule of locus standi in Malaysia and how it has become the major obstacle in promoting public interest litigation. This research compares the position of the approach of the rule of locus standi in Malaysia, India and United Kingdom. The study comprises of two prime objectives which are to carry out a comparative study on the rale of locus standi in Malaysia, India and United Kingdom and to promote the development of public interest litigation by liberalizing the rule of locus standi in Malaysia. Based on this research, we have formed our own understanding of the importance in liberalizing the strict rule of locus standi in Malaysia.